HEM 2020
DOI: 10.21272/hem.2020.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Of The Responsible Investments Instruments In Sdg 3 ‘Good Health And Well-Being’ Financing: EU And US Experience

Abstract: This article summarizes the existing approaches to investigating instruments of responsible investments in the health care system in Europe and in United States. The main research’s purpose is to identify existing instruments of responsible investment under funding Sustainable Development Goal 3: ‘Good health and well-being’. Systematization of scientific sources and approaches on the investigated issue showed no unique approach to forming a list of responsible investment instruments to finance health and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Undoubtedly, when opening own business, you may encounter many traditional obstacles, for example, capital limitations and the search for additional investments, business partners and lack of confidence in opening a new business, risks related to the competitors' activities in a particular business environment. However, all mentioned factors set the tone for readiness to be an active participant in the business environment (Serpeninova et al, 2020). It is important to understand the ability to adapt educational services to the requirements of the modern labor market (Delibasic et al, 2022;Zuluaga-Ortiz et al, 2022;Draskovic et al, 2020;Hitka et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Undoubtedly, when opening own business, you may encounter many traditional obstacles, for example, capital limitations and the search for additional investments, business partners and lack of confidence in opening a new business, risks related to the competitors' activities in a particular business environment. However, all mentioned factors set the tone for readiness to be an active participant in the business environment (Serpeninova et al, 2020). It is important to understand the ability to adapt educational services to the requirements of the modern labor market (Delibasic et al, 2022;Zuluaga-Ortiz et al, 2022;Draskovic et al, 2020;Hitka et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, there is no unified understanding of the role of the shadow economy in the functioning of the economy and ensuring its stability. According to the results of the paper's analysis, it can be concluded that the shadow economy negatively affects certain sectors of economic development and the attractiveness of Lithuania (Ginevicius et al, 2021), Ukraine (Kuznyetsova et al, 2017;Shpak et al, 2022), Algeria (Ramli et al, 2022), EU countries (Roszko-Wójtowicz & Grzelak, 2020;Serpeninova et al, 2020;Vasanicova et al, 2022), Croatia (Škare et al, 2020), BRICS (Cheteni, P. & Umejesi, 2022;Tsaurai, 2022); Central Asia and Eastern Europe (Kaya & Engkuchik, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, if tax credits are the main incentive, firms reduce (increase) their share of R&D expenditures while strengthening (weakening) credit [1]. Kobushko et al (2017) [2], Sineviciene et al (2018) [3], Miuller, Kuznetsova et al (2021) [4], Serpeninova et al (2020) [5] investigated promoting and financing innovation to increase the economic growth, security and sustainable development. Gil & Iglésias (2020) determined the long-term effects of inflation and monetary policy in the growth model, including indicators of R&D, real interest rate, economic growth, investment rate etc.…”
Section: Literature Reviewmentioning
confidence: 99%